Infection Due to 3 Avian Influenza Subtypes in United States Veterinarians - Myers, Kendall P. (2007)
BACKGROUND: Pandemic influenza virus strains originate in avian species. We examined veterinarians in the United States for evidence of previous avian influenza virus infection. METHODS: We performed a controlled, cross-sectional seroprevalence study among 42 veterinarians and 66 healthy control subjects using serum samples collected from 2002 through 2004. Serum samples were tested using a microneutralization assay against 9 influenza A virus strains. RESULTS: Using multivariable logistic regression modeling, veterinarians exposed to birds demonstrated statistically significant elevated titers against the H5, H6, and H7 avian influenza virus isolates, compared with control subjects. CONCLUSIONS: These data suggest that occupational exposure to avian species may increase veterinarians’ risk of avian influenza virus infection. Veterinarians should be considered for priority access to vaccines and antiviral drugs in pandemic planning.